Indonesian Herb Extracts Inhibit the Replication of Bovine Respiratory Syncytial Virus: In Vitro Study - Priosoeryanto, Bambang Pontjo; Sudaryatma, Putu Eka; Lanniari, Nafrina; Setiyaningsih, Surachmi; Harlina, Eva; Wulansari, Retno; Ridho, Rachmi; Rostantinata, Riski; Wiradana, Putu Angga; Okabayashi, Tamaki (HAYATI Journal of Biosciences, 2025)
Bovine respiratory syncytial virus (BRSV) is highly prevalent in cattle. It is a major viral cause of bovine respiratory disease complex, which is associated with morbidity, mortality and substantial economic impact. Currently available treatments are only symptomatic, but no specific treatments are available for BRSV infection. This study aimed to identify new antiviral agents against BRSV, which could be used to control bovine respiratory disease complex in cattle with Indonesian herb extracts. Ethanol extracts prepared from Indonesian herbs including Andrographis paniculata, Phyllanthus niruri, Curcuma aeruginosa, and Curcuma xanthorrhiza were evaluated for anti-BRSV activity in A549 cells. The cytotoxicity of the herb extracts was evaluated using a CCK-8 cell viability assay. Antiviral activities of the herb extracts were examined using cell activity and cytopathic assays. The effect on virus production was evaluated by qRT-PCR and plaque-formation assays. Extracts of Curcuma xanthorrhiza (125 μg/ml), Andrographis paniculata (250 μg/ml), and Phyllanthus niruri (62.5 μg/ml) inhibited BRSV activity in A549 in pre-, simultaneously-, and post-infection treatment assays, respectively, as measured by the selective index. Reduction of BRSV activities by the herb extracts correlated with inhibition of viral gene expression and inhibition of plaque formation in a concentration- and time-dependent manner. Our findings suggest that these herb extracts have sufficient potency to be used not only as a therapeutic agent but also as a preventive agent to limit BRSV infection.